PENERAPAN MODEL PEMBELAJARAN MATEMATIKA KNISLEY TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS X MIPA SMA NEGERI 1 PAYAKUMBUH - Fauziah Annisa Rahma (Jurnal Edukasi dan Penelitian Matematika, 2022)
One of the outcomes of learning mathematics that students must have is the capacity to comprehend mathematical concepts. However, class X MIPA students at SMA Negeri 1 Payakumbuh still have a poor understanding of mathematical principles. The goal of this study was to ascertain and evaluate whether students in class X MIPA SMA Negeri 1 Payakumbuh who were taught using the Knisley mathematics learning model had a greater understanding of mathematical topics than students who were taught using traditional methods. A quasi-experimental research design with a non-equivalent posttest only control group design was used in this study. Based on data analysis, it was found that students in class X MIPA at SMA Negeri 1 Payakumbuh who learned using the Knisley mathematics learning model were better able to understand mathematical ideas than students who studied conventionally. Keywords– Knisley, Mathematical Concepts Understanding